Plant spacing and cultivar effect on industrial hemp growth, biomass, and cannabinoids yield - Deepak Khatri; Saroop S. Sandhu; Flint Johns; Hardev Sandhu; Anuj Chiluwal (Agrosystems, Geosciences & Environment)
Abstract There is rising interest in the United States for industrial hemp (Cannabis sativa L.) cultivation as a new cash crop after the recent reversal of its production ban. Due to limited research during its long prohibition, little information is available regarding its optimal cropping system and crop management practices. Hence, the study was conducted to identify the optimal plant spacing for two cannabidiol (CBD)‐dominant industrial hemp cultivars (BaOX and Wife) in Florida. Three plant spacing treatments, that is, 61 cm (24 in.), 91 cm (36 in.), and 122 cm (48 in.), were used with a common row spacing of 1.52 m. Plant height, chlorophyll content using soil plant analysis development 502, and canopy cover using Canopeo were recorded every 2‐weeks interval throughout the crop growing season. The final biomass yield, CBD, and delta‐9‐tetrahydrocannabinol (THC) yield were also recorded. The results showed no significant differences between the cultivars in biomass, CBD yield, and plant growth and physiological parameters in most of the observations. Plant height and chlorophyll content were mostly unaffected by spacing. Canopy cover was higher during most of the growing season at lower spacing. Dry biomass yield per plant was higher with wider spacing, but there was no significant difference in total biomass yield per unit area. Wider spacing (91 and 122 cm) also resulted in higher CBD and THC yield in one of the tested cultivars (BaOX). The results suggest that wider plant spacing in industrial hemp could help maximize CBD production in Florida and other regions with similar environmental conditions.